2012
DOI: 10.1007/s11746-012-2030-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an HPLC–DAD Method for Analysis of the Six Major Isoflavones in Extracts from Soybean Processing

Abstract: In this study, a new HPLC method was developed and validated for the determination of daidzin, genistin, glycitin, and their respective aglycones daidzein, genistein and glycitein in extracts from different stages of soy processing. The chromatographic separation was achieved using a Bonus RP 100 9 3.0 mm (3.5-lm particle size) column maintained at 35°C. The mobile phase consisted of a gradient of water and acetonitrile both containing 0.1% formic acid. Analyses were conducted at a flow rate of 1.0 mL min -1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The most frequently used solvent mixture for the extraction of the 12 major forms of isoflavones from soybeans and their derivatives is 80% aqueous methanol (Cavaliere and others ; Fiechter and others ; Hong and others ; Aguiar and others ; Gasparetto and others ; Fahmi and others ; Fonseca and others ; López‐Gutiérrez and others ; Verardo and others ). In very few cases pure methanol is used to carry out the extraction (Otieno and others ).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The most frequently used solvent mixture for the extraction of the 12 major forms of isoflavones from soybeans and their derivatives is 80% aqueous methanol (Cavaliere and others ; Fiechter and others ; Hong and others ; Aguiar and others ; Gasparetto and others ; Fahmi and others ; Fonseca and others ; López‐Gutiérrez and others ; Verardo and others ). In very few cases pure methanol is used to carry out the extraction (Otieno and others ).…”
Section: Sample Preparationmentioning
confidence: 99%
“…In the development of the HPLC method, it was observed that the use of acetonitrile as an organic modifier resulted in a better resolution of cyclolinopeptides compared to methanol. Furthermore, the use of methanol resulted in undesirable baseline drifts in the gradient profile [24]. Previous HPLC separation by Brühl et al [15] using methanol/water was only able to separate five CLPs.…”
Section: Efficiency Of Clps Extractionmentioning
confidence: 99%
“…+ , 539[M + Na] + , 517[M + H] + , 255[M + H-Suc-Glu] + + , 271[M + H] + [19,24,26,27,29,33] + , 455[M + Na] + , 433[M + H] + , 271[M + H-Glu] + + , 455[M + Na] + , 433[M + H] + , 271[M + H-Glu] +[19,24,26,27,29,33] …”
mentioning
confidence: 99%